Les écoles néo-nurcu de Fethullah Gülen en Asie centrale : implantation, fonctionnement et nature du message véhiculé par le biais de la coopération éducative - Bayram Balci (Revue des Mondes Musulmans et de la Méditerranée)
Since the break up of USSR, Turkic Central Asia - Uzbekistan, Turkmenistan, Kazakhstan et Kyrgyzstan - emerged on the geopolitical scene and fed the identity debate in Turkey. Although the Turkish state grants these republics a new and high geopolitical importance, Turkish presence in the region results more from the commitment of private actors, among which one should distinguish the community of Fethullah Gülen, leader of a branch of the nurcu movement funded by Said Nursi (1873-1960). On the eve of independence in Central Asia, the community of Fethullah Gülen stands at the peak of its power and influence in Turkey. It benefits from a large and powerful educational network that serves its implementation strategy for Central Asia. With the support of businessmen and missionary education professionals, this community inaugurates as soon as September 1991 dozens of private schools run by nurcu professors together with their Central Asian partners. Businessmen from Turkey and Central Asia provide the financial support necessary for the development of such schools, out of which will emerge the next elites of the nation with a close relationship to the movement. Like any missionary movement, the group of Fethullah Gülen carries an ideology and spreads a message for the dissemination of an Islam based on modernity and slightly tinged with mysticism. Spreading Islamic ethics is definitely the priority motivation for nurcu missionaries in Central Asia. However, because of the strong suspicion and paranoia among those post-Soviet states against any kind of religious movement, nurcu schools in order to strengthen their presence focus more on turcity than on Islamic ethics. Their contribution to the dissemination of turcity explains the good relations this religious community has been maintaining with the Turkish state in Central Asia while their relations are very much problematic in Turkey. Whereas very much appreciated in Central Asia for their education activities, Gülen's movement has no guarantee for sustainability in the region. Indeed, today the majority of its missionaries are Turkish expatriates from Anatolia. The education of local elites will take more time, as it will depend from the rapidity with which the new regimes will move towards more tolerance and freedom for all political and religious trends and movements.